Energy Optimization and Protection of 3-Phase Electrical Systems Based on IoT - Ratuhaji, Faruq; Mantasia, Mantasia (Jambura Journal of Electrical and Electronics Engineering, 2025)
Three-phase electrical systems have advantages in efficiency and power stability but are susceptible to voltage disturbances such as overvoltage and undervoltage. Overvoltage is a condition where the voltage exceeds the upper threshold, while undervoltage occurs when the voltage drops below the minimum limit. Both of these conditions can lead to decreased efficiency, equipment damage, and operational disruptions. Therefore, an adaptive protection system capable of detecting abnormal conditions in real-time is needed. This research develops a three-phase electrical monitoring and protection system based on the Internet of Things (IoT). The system uses a PZEM-004T sensor to read the voltage and current on each phase, with the ESP32 microcontroller as the data processor and protection controller. Information is sent to the web-based user interface via a Wi-Fi network. Users can monitor system conditions online through a monitoring website that displays voltage and current parameters in real-time, as well as fault notifications. The test results indicate that the system accurately measures voltage and current, with average errors of just 0.35% and 0.45%, and it can automatically reduce power load within 5 to 6 seconds when there is a problem, while also sending real-time alerts about any issues through a web-based interface. Thus, this system is suitable for application in household and light industrial installations. Besides improving energy efficiency and the reliability of the electrical system, this system also promotes the utilization of IoT technology in modern electricity. Further research is recommended to develop a system with short-circuit current detection, harmonic analysis, and integration into a smart grid.Sistem kelistrikan tiga fasa memiliki keunggulan dalam efisiensi dan kestabilan daya, namun rentan terhadap gangguan tegangan seperti overvoltage dan undervoltage. Overvoltage adalah kondisi saat tegangan melebihi ambang batas atas, sedangkan undervoltage terjadi saat tegangan turun di bawah batas minimal. Kedua kondisi ini dapat menyebabkan penurunan efisiensi, kerusakan peralatan, dan gangguan operasional. Oleh karena itu, dibutuhkan sistem proteksi yang adaptif dan mampu mendeteksi kondisi abnormal secara real-time. Penelitian ini mengembangkan sistem monitoring dan proteksi kelistrikan tiga fasa berbasis Internet of Things (IoT). Sistem menggunakan sensor PZEM-004T untuk membaca tegangan dan arus pada masing-masing fasa, dengan mikrokontroler ESP32 sebagai pengolah data dan pengendali proteksi. Informasi dikirim ke antarmuka pengguna berbasis web melalui jaringan Wi-Fi. Pengguna dapat memantau kondisi sistem secara daring melalui website monitoring yang menampilkan parameter tegangan, arus secara real time, serta notifikasi gangguan. Hasil pengujian menunjukkan bahwa sistem memiliki akurasi pembacaan tegangan dan arus yang sangat baik dengan masing-masing nilai rata-rata Mean Absolute Percentage Error (MAPE) 0,35% dan 0,45%, dan waktu respon otomatis pemutusan beban ketika terjadi gangguan dalam rentang 5 hingga 6 detik, disertai dengan pengiriman informasi kondisi abnormal secara real-time melalui antarmuka berbasis web. Dengan demikian sistem ini layak diterapkan pada instalasi rumah tangga dan industri ringan. Selain meningkatkan efisiensi energi dan keandalan sistem kelistrikan, sistem ini juga mendorong pemanfaatan teknologi IoT dalam kelistrikan modern. Penelitian selanjutnya direkomendasikan untuk mengembangkan sistem dengan deteksi arus hubung singkat, analisis harmonisa, serta integrasi ke jaringan listrik pintar (smart grid).